2019
DOI: 10.1007/s10853-019-03509-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface mechanical treatment on the oxidation behavior of FeAl-model alloy

Abstract: Fe-based alloys are commonly used in almost every sector of human life. For different reasons, the surfaces of the real parts are prepared using different methods, e.g., mirror-like polishing, grit-blasting, etc. The purpose of the present work is to answer the question how the surface preparation influences the oxidation behavior of Fe-based alloys. To answer this question, a high-purity model alloy, Fe-5 wt%Al, was isothermally oxidized in a thermogravimetrical furnace. The post-exposure analysis included SE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…One can notice that the difference in the R a parameter values was about one order of magnitude higher for the grit-blasted surface as compared to the ground one. This observation is in agreement with the literature data [17,18].…”
Section: Methodssupporting
confidence: 94%
“…One can notice that the difference in the R a parameter values was about one order of magnitude higher for the grit-blasted surface as compared to the ground one. This observation is in agreement with the literature data [17,18].…”
Section: Methodssupporting
confidence: 94%
“…Another proposed explanation of different oxidation behavior of studied material is that more rough surface preparation introduces higher amount of defects which can act as an easy diffusion path for the elements forming protective oxide scale (Cr, Mn and Si in the present case) as it was already proposed in previous works (Ref [21][22][23][24]34). For quantitative description of the influence of surface geometry in term of surface roughness, time-to-failure was calculated for each specimen tested in all kind of cyclic oxidation test.…”
Section: Discussionmentioning
confidence: 72%
“…The increase in oxidation resistance can be achieved by applying of oxidation resistant coatings like, e.g., aluminide layers (Ref [11][12][13][14] or MCrAlY-type coatings (Ref [15][16][17][18], however, this is an additional process which generates additional costs. It was already shown that by the simple surface preparation methods resulting in different surface roughness, high temperature oxidation kinetics of metallic materials can be affected (Ref [19][20][21][22][23][24][25]. The effect of surface preparation of AISI 316Ti on its wet corrosion resistance was already studied ( Ref 26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Since there is no interface separating the surface layer and the substrate, the problem of poor interface bonding between the nanostructured surface layer and the substrate, usually caused by traditional coating techniques, is easily solved ( Nana & Ning, 2018 ; Du et al, 2019 ). In addition, SMAT materials have the advantages of high strength, high hardness, high diffusion rate and high chemical reactivity, and their wear resistance and fatigue resistance are also significantly improved ( Nowak, Serafin & Wierzba, 2019 ; Benafia, Retraint & Brou, 2018 ; Yao et al, 2017 ; Fang et al, 2011 ; Wang & Lu, 2017 ; Tong et al, 2003 ; Wang et al, 2003 ; Lei et al, 2019 ; Lu & Lu, 2004 ). In this study, the influence of surface morphologies on the adhesion, proliferation and differentiation of hBMSCs might be safely excluded, while the samples in the experimental and controlled groups show a similar surface morphology (with surface roughness R a of 1.73 ± 0.11 and 1.82 ± 0.06 μm, respectively).…”
Section: Discussionmentioning
confidence: 99%